Must Trust Bust? - Peter Møllgaard (Copenhagen Business School (CBS), Department of Economics, 2002)
Our trust in competition policy is based on faith in markets. When markets are oligopolies, already classical economists' trust in competition busted: Oligopolies carry the seeds of collusion. To develop, collusion needs trust between firms. But new leniency programmes are designed to bust that trust. I discuss when trust busters are likely to succeed and when trust prevails.
hdl:10398/7646
Keywords: G10; G18; L13; 330; Competition policy; Oligopolies; Collusion; Trust; Leniency programmes